Impact of 2‐Weeks Continuous Increase in Retrograde Shear Stress on Brachial Artery Vasomotor Function in Young and Older Men - Thijssen, Dick H. J. (J Am Heart Assoc, 2015)
BACKGROUND: Although acute elevation in retrograde shear rate (SR) impairs endothelial function, no previous study has explored the effect of prolonged elevation of retrograde SR on conduit artery vascular function. We examined the effect of 2‐weeks elevation of retrograde SR on brachial artery endothelial function in young and in older men. METHODS AND RESULTS: Thirteen healthy young (23±2 years) and 13 older men (61±5 years) were instructed to continuously wear a compression sleeve around the right forearm to chronically (2 weeks) elevate brachial artery retrograde SR in 1 arm. We assessed SR, diameter, and flow‐mediated dilation in both the sleeve and contralateral control arms at baseline and after 30 minutes and 2 weeks of continuous sleeve application. The sleeve intervention increased retrograde SR after 30 minutes and 2 weeks in both young and older men (P=0.03 and 0.001, respectively). In young men, brachial artery flow‐mediated dilation % was lower after 30 minutes and 2 weeks (P=0.004), while resting artery diameter was reduced after 2 weeks (P=0.005). The contralateral arm showed no change in retrograde SR or flow‐mediated dilation % (P=0.32 and 0.26, respectively), but a decrease in diameter (P=0.035). In older men, flow‐mediated dilation % and diameter did not change in either arm (all P>0.05). CONCLUSIONS: Thirty‐minute elevation in retrograde SR in young men caused impaired endothelial function, while 2‐week exposure to elevated levels of retrograde SR was associated with a comparable decrease in endothelial function. Interestingly, these vascular changes were not present in older men, suggesting age‐related vascular changes to elevation in retrograde SR.